Deteksi Perubahan Berat Badan Akseptor KB Hormonal dengan Menggunakan Model Regresi Linear Berganda - Reni Saswita; Nurbaity Nurbaity; Untari Anggeni (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Hormonal contraception, which uses estrogen and progesterone preparations, is a contemporary method of contraception that is popular among active birth control participants. Apart from stopping population growth, it also has negative effects on its users. The side effect of increasing body weight can occur due to the nature of the acceptor and the use of hormonal contraceptives for a long period of time. The aim of the study was to detect changes in body weight of hormonal birth control acceptors based on age, parity and length of use of contraception using a multiple linear regression model. Non-experimental quantitative analytical research method with a cross sectional design. The research was conducted at several PMBs in Palembang City in July-September 2023 with samples consisting of hormonal birth control acceptors taken using a purposive sampling technique. Data were collected using questionnaires and body weight measurements and analyzed by multiple linear regression. The results of the research show that the prediction model for weight change = 5.789 - 0.098 Age + 1.4 Parity - 0.008 Length of birth control. Weight gain will definitely affect the health of the recipient and can increase the risk of obesity if it continues. To maintain a stable weight, birth control acceptors must pay attention to their daily diet and exercise regularly. It is very important to obtain information about the effects caused by the use of hormonal birth control with a high number of parities and ages at risk.